Moving to 3-D flood hazard maps for enhancing risk communication. (January 2019) - Macchione, Francesco; Costabile, Pierfranco; Costanzo, Carmelina; De Santis, Rosa
Abstract: 3-D representations of flood inundation through emerging formats in virtual and augmented realities may be a powerful tool with which to interact with political decision-makers and to engage people with flood hazards. Despite that, environmental scientists are far from fully harnessing these techniques when interacting with non-scientists. Integrations with computer graphic science is considered necessary to such an extent that a distinct and emerging field of research related to the visualization in assisting environmental scientists can be detected in the literature. A key issue could be represented by the implementation of a simple visualization product that can be used by hydraulic engineers as a reasonable balance between the intrinsic informatics complexity of virtual reality and the practical need to represent flooding events in 3-D environments for risk communication purposes. Therefore, this paper aims at defining a suitable path that starts from the river model set-up and, passing through 2-D flood simulations obtained by means of shallow water equations, arrives at 3-D visualizations of the results. In particular, this paper is focused on developing an intentionally simple workflow for the representation of two-dimensional hydraulic simulations within a 3-D virtual reality environment. The level of detail as well as the pro and cons associated with the use of this procedure are discussed and the appropriateness of visualization outputs of the proposed procedure are analysed. These issues are discussed with reference to a case study located in the old town of Cosenza (Calabria, Italy). Highlights: Representation of two-dimensional hydraulic simulations within a 3-D virtual reality environment. Rendering of a 3-D urban environment and simulated flooded areas using Blender scenes. Perspectives on use of 3-D visualization outputs to satisfy the needs of different end-users groups in flood risk management.